1971
DOI: 10.1085/jgp.57.6.752
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Norepinephrine and Dibutyryl Cyclic Adenosine Monophosphate on Cation Transport in Duck Erythrocytes

Abstract: Freshly prepared duck erythrocytes, incubated either in plasma or an isotonic synthetic medium containing norepinephrine ([K] of both media 2.5 m), maintain water and electrolyte composition in the steady state (upper steady state) for at least 90 min. If incubated in the synthetic medium without norepinephrine or in plasma to which a -adrenergic blocking agent (propranolol) is added, the cells lose both water and electrolyte (predominantly KCI) until a new steady state is reached (lower steady state). Reaccum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 15 publications
8
53
0
Order By: Relevance
“…Table III illustrates the effect of ouabain on cell water and ion contents during a 3-h incubation in isotonic solutions. In the absence of the drug, these preincu-bated cells usually continue to lose 2% of their water over the next 3 h. This is in contrast to the apparent steady state achieved by Muscovy duck red cells as reported by Riddick et al (1971). Kregenow (1973), however, has observed a similar 2% shrinkage of Muscovy duck cells under these circumstances.…”
Section: Osmolality Ph and Ion Measurementsmentioning
confidence: 64%
See 1 more Smart Citation
“…Table III illustrates the effect of ouabain on cell water and ion contents during a 3-h incubation in isotonic solutions. In the absence of the drug, these preincu-bated cells usually continue to lose 2% of their water over the next 3 h. This is in contrast to the apparent steady state achieved by Muscovy duck red cells as reported by Riddick et al (1971). Kregenow (1973), however, has observed a similar 2% shrinkage of Muscovy duck cells under these circumstances.…”
Section: Osmolality Ph and Ion Measurementsmentioning
confidence: 64%
“…These effects have also been studied in red cells from the Muscovy duck (Cairina raoschata) by Riddick and by Kregenow. Although propranolol effectively prevents the swelling response to catecholamine (Riddick et al, 1971), this /3-adrenergic blocker has no effect on reswelling in hypertonic solutions (Kregenow, 1971). The two systems demonstrate important similarities.…”
Section: Introductionmentioning
confidence: 98%
“…Previous reports in avian red cells indicated that catecholamines stimulate a cAMPdependent transport mechanism similar to that of the avian VRI response (Riddick et al, 1971 ;Kregenow, 1973;Kregenow et al, 1976). The possibility that hypertonicity and catecholamine-stimulated salt transport in avian and amphibian red cells may have common characteristics was anticipated by the work of Orskov (1954Orskov ( , 1956a.…”
Section: Discussionmentioning
confidence: 94%
“…Cells for gravimetric cell volume determination were removed from the top of the special tubes with a Pasteur pipette . The cell pellet was then weighed, dried at 60°C to constant weight (at least 12 h), cooled in a dessicator, and reweighed for the dry weight determination (Riddick et al ., 1971) . To obtain cells for chemical or tracer ion measurements, the plug was removed and the cells were washed out with deionized water through the opening at the base into a centrifuge tube .…”
Section: Methodsmentioning
confidence: 99%
“…He found that norepinephrine and, to a lesser extent, epinephrine stimulated net potassium uptake in pigeon red cells in vitro. Riddick et al (1971) suggested that norepinephrine -is actually required for Muscovy duck red cells to maintain steady states of ions and water at normal levels in artificial, buffered salt solutions. Omission of the hormone from their incubations resulted in a spontaneous decline in cell potassium and water until a THE JOURNAL OF GENERAL PHYSIOLOGY • VOLUME 70 -1977 new "lower steady state" was reached after 90 min.…”
Section: Introductionmentioning
confidence: 99%